Increased illness burden in women with comorbid bipolar and premenstrual dysphoric disorder: data from 1 099 women from STEP‐BD study. (28th August 2017) - Slyepchenko, A.; Frey, B. N.; Lafer, B.; Nierenberg, A. A.; Sachs, G. S.; Dias, R. S.
Abstract : Background: The impact of comorbid premenstrual dysphoric disorder (PMDD) in women with bipolar disorder (BD) is largely unknown. Aims: We compared illness characteristics and female‐specific mental health problems between women with BD with and without PMDD. Materials & Methods: A total of 1 099 women with BD who participated in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP‐BD) were studied. Psychiatric diagnoses and illness characteristics were assessed using the Mini International Neuropsychiatric Interview. Female‐specific mental health was assessed using a self‐report questionnaire developed for STEP‐BD. PMDD diagnosis was based on DSM‐5 criteria. Results: Women with comorbid BD and PMDD had an earlier onset of bipolar illness ( P < 0.001) and higher rates of rapid cycling ( P = 0.039), and increased number of past‐year hypo/manic ( P = 0.003), and lifetime/past‐year depressive episodes ( P < 0.05). Comorbid PMDD was also associated with higher proportion of panic disorder, post‐traumatic stress disorder, generalized anxiety disorder, bulimia nervosa, substance abuse, and adult attention deficit disorder (all P < 0.05). There was a closer gap between BD onset and age of menarche in women with comorbid PMDD ( P = 0.003). Women with comorbid PMDD reported more severe mood symptoms during the perinatal period and while taking oral contraceptives ( P < 0.001). Discussion: The results from this study is consistent with research suggesting that sensitivity to endogenous hormones may impact the onset and the clinical course of BD. Conclusions: The comorbidity between PMDD and BD is associated with worse clinical outcomes and increased illness burden.